Low temperature epitaxial silicon film growth using high vacuum electron-cyclotron-resonance plasma deposition - Chumanov, George, author; Dalal, Vikram L., author; DeBoer, Scott J., author; Bartels, Randy, author; American Institute of Physics, publisher (Colorado State University. Libraries, 1995)
We report on the growth technique and electrical properties of epitaxial Si films grown at low temperatures using an electron-cyclotron-resonance plasma deposition technique. We have used standard high vacuum apparatus to grow high quality films at 450-525 °C. A critical step in achieving high quality films is an in situ hydrogen plasma cleaning of the wafer before growth. We have systematically studied the influence of ion bombardment during growth by biasing the substrate, and find that the films are crystalline for substrate bias voltages less negative than about -15 V, but become polycrystalline as the magnitude of the negative bias is increased. The crystallinity of the film was measured using Raman spectroscopy. The undoped films are n type with carrier concentrations in the 1016-1017 cm-3 range. The Hall mobilities measured for the films are comparable to values obtained in bulk Si crystals. We can achieve abrupt profiles in carrier concentrations between the heavy doped substrate and the epilayer, with no evidence of diffusion.
Keywords: crystal doping; chemical vapor deposition; ECR heating; plasma; epitaxy; silicon; surface cleaning; carrier density; carrier mobility; Hall effect